2013
DOI: 10.1002/adsc.201300299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,4‐Disubstituted Quinolin‐2‐(1H)‐ones via Palladium‐Catalyzed Decarboxylative Arylation Reactions

Abstract: The Pd-catalyzed decarboxylative crosscoupling reaction of 4-substituted quinolin-2(1H)one-3-carboxylic acids with (hetero)aryl halides is described. With palladium(II) bromide and triphenylarsine ligand as the catalyst system, a variety of 4substituted 3-(hetero)aryl quinolin-2A C H T U N G T R E N N U N G (1 H)-ones and related heterocycles, such as 4-substituted 3-arylcoumarins can be prepared in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…3-(4-Chlorophenyl)-4-(4-methoxyphenyl)-1-methylquinolin-2(1H)-one (4e). 25 Following the general procedure, 3e was purified by silica gel chromatography (10% EA/PE) to give a yellow solid, 76.5 mg, yield: 51%, mp 194−195 °C. 6, 159.0, 147.8, 139.6, 134.7, 132.7, 132.1, 131.1, 130.9, 130.5, 128.6, 128.2, 127.8, 122.0, 121.7, 114.1, 113.6, 55.2, 30 4-(4-Chlorophenyl)-3-(4-methoxyphenyl)-1-methylquinolin-2(1H)-one (4f).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-(4-Chlorophenyl)-4-(4-methoxyphenyl)-1-methylquinolin-2(1H)-one (4e). 25 Following the general procedure, 3e was purified by silica gel chromatography (10% EA/PE) to give a yellow solid, 76.5 mg, yield: 51%, mp 194−195 °C. 6, 159.0, 147.8, 139.6, 134.7, 132.7, 132.1, 131.1, 130.9, 130.5, 128.6, 128.2, 127.8, 122.0, 121.7, 114.1, 113.6, 55.2, 30 4-(4-Chlorophenyl)-3-(4-methoxyphenyl)-1-methylquinolin-2(1H)-one (4f).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…1, 128.0, 127.8, 122.0, 121.3, 114.2, 113.2, 55.1, 30.2 3-(4-Chlorophenyl)-1-methyl-4-phenylquinolin-2(1H)-one (4g). 25 Following the general procedure, 4g was purified by silica gel chromatography (15% EA/PE) to give a yellowish solid, 98.0 mg, yield: 71%, mp 205−207 °C. 1 H NMR (600 MHz, CDCl 3 ) δ 7.58 (t, J = 8.0 Hz, 1H), 7.45 (d,J = 8.5 Hz,1H),4H),3H), 7.09 (dd, J = 7.5, 2.0 Hz, 2H), 7.04 (d, J = 8.5 Hz, 2H), 3.84 (s, 3H).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2 Considering the important activity of 3-substituted quinoxalin-2(1 H )-one compounds, increasing numbers of scholars are studying methods for their synthesis. In recent years, reports have shown that great progress has been made in arylation, 3` b c d e f g h i j acylation, 3k–l amination, 3m–q alkylation, 3` s t u v and phosphonylation 3` x at position 3 of quinoxalin-2(1 H )-ones. Among them, the use of styrene bifunctionalization to realize the functionalization of quinoxalin-2(1 H )-ones at C3 has become a new synthetic trend.…”
Section: Table 1 Optimization Of Reaction Conditions ...mentioning
confidence: 99%
“…In the last few decades, some strategies were reported for the transition metal catalyzed decarboxylative coupling reactions . In this context, the Pd-catalyzed decarboxylative coupling reaction of quinolinone-3-carboxylic acids and related heterocyclic carboxylic acids with aryl halide were conducted in the presence of Pd­(II)/triphenylarsine catalytic system (Scheme b) . Also, a rhodium-catalyzed selective C-4 alkenylation of 2-pyridones including a directing group was demonstrated by Hirano and co-workers …”
Section: Introductionmentioning
confidence: 99%